Analysing Viewpoints Of Parents Regarding Marriage Of Their Sons And Daughters With Intellectual Disabilities In The City Of Jeddah, Kingdom Of Saudi Arabia - Alzahrani, Nasser (International Journal of Psychosocial Rehabilitation, 2024)
This study aims to analyse the views of parents of persons with Intellectual Disability aboutthe marriage of their children in the Saudi society. This study was applied in the city ofJeddah in the Kingdom of Saudi Arabia due to the cultural diversity there and the differentcommunity customs and traditions. The study used data collected from 30 parents. Thissample was randomly selected from different neighbourhoods in Jeddah. The research usesa quantitative survey questionnaire to analyse the views of parents. The study sampleincluded a number of parents of persons with Intellectual Disabilities both males andfemales. Perspectives were analysed on marriage of persons with Intellectual Disabilities,the source of concern about their marriages and the potential impact of marriage on hismental and emotional state. The results of the research show that parents adhere to theviews that their sons and daughters with Intellectual Disabilities should marry. However,there is a need for more studies and research on the subject of marriage for people withspecial needs from other categories such as people with visual impairments , Hearingdisability and people with autism disorders from the feasibility of marriage for peoplewith special needs and its psychological, moral and social impact on them.